Public Charging Infrastructure and the Market Diffusion of Electric Vehicles - Ulrike Illmann; Jan Kluge (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2019)
A comprehensive roll-out of public charging infrastructure will be costly. However, its impact on the diffusion of electric vehicles (EVs) is not clear at all. Our study aims at estimating the extent to which an increasing availability of public charging infrastructure promotes consumers' decisions to switch to EVs. We make use of a German data set including monthly registrations of new cars at the ZIP-code level between 2012 and 2017 and match it with the official registry of charging stations. We measure charging infrastructure by its visibility, capacity and abundance in order to estimate its impact on EV adoption. A CS-ARDL approach is deployed in order to identify the structural long-run relationship between charging infrastructure and monthly EV registrations. There is evidence of a positive long-run relationship but on a rather low scale. We conclude that consumers do not necessarily react to the mere number of chargers but attach more importance to charging speed.
Keywords: L90; O18; O33; R42; 330; Electric vehicles; charging infrastructure; CS-ARDL